Contemporary Processes of Large-Scale Land Acquisition in Sub-Saharan Africa: Legal Deficiency or Elite Capture of the Rule of Law? - German, L.; Schoneveld, George C.; Mwangi, E. (Elsevier, 2013)
Growth of emerging economies, policy commitments to biofuels and volatility in commodity prices have contributed to a marked increase in the pace and scale of foreign direct investment in land-based enterprises in the global South. This paper explores the relationship between policy and practice associated with customary rights protections in the context of large-scale land acquisitions through a document review and case study analyses from Ghana, Mozambique, Tanzania, and Zambia. Findings point to the difficulty of safeguarding customary rights even in countries providing “best practice” legal protections, and point to the fundamental role of human agency in shaping outcomes.